Carbon dynamics and CO2 and CH4 exchange in the mangrove dominated Guayas river delta, Ecuador. (5th April 2022) - Belliard, Jean-Philippe; Hernandez, Simon; Temmerman, Stijn; Suello, Rey Harvey; Dominguez-Granda, Luis E.; Rosado-Moncayo, Andrea M.; Ramos-Veliz, John A.; Parra-Narera, Rebeca N.; Pollete-Ramirez, Karem; Govers, Gerard; Borges, Alberto V.; Bouillon, Steven
Abstract: Although estuaries are considered important pathways in the global carbon cycle, carbon dynamics in tropical estuaries is relatively understudied. Here, the tidal, seasonal and spatial variability of particulate organic carbon (POC), dissolved inorganic carbon (DIC), carbon dioxide (CO2 ) and methane (CH4 ), among other biogeochemical variables related to carbon cycling, were studied in the Guayas river delta (Ecuador) to document the sources, processing and fluxes of these carbon forms. All variables were studied during a semi-diurnal (13 h) tidal cycle and along river transects at low and high tides, all carried out during one dry and rainy season. POC and total suspended matter (TSM) strongly covaried and peaked at high tidal flow velocities during a tidal cycle and at high river discharge during the rainy season, suggesting that resuspension of bottom sediments and/or surface erosion in the river catchment were a dominant source of particulate matter in the water column. The δ 13 C of POC, (from ∼-22‰ to ∼-27‰) showed an increasing contribution of marine phytoplankton to the POC pool as moving downstream along the delta during the dry season. Upstream DIC concentrations (∼1200 μmol L −1 ) were high in the Guayas river delta as compared to other tropical estuarine systems, and the δ 13 C of DIC revealed a shift from a more phytoplankton dominated source in the dry season and downstream (∼-4‰) to a relatively more terrestrial source in the rainy season and upstream (∼-12.5‰). Both DIC and its δ 13 C showed slight but consistent deviations from conservative mixing that hint at inputs of 13 C depleted DIC from mineralization along the delta. High values of the partial pressure of CO2 ( p CO2 ) observed upstream and in the rainy season (∼5250 μatm), associated with O2 undersaturation (∼60%) and low δ 13 CDIC, suggest a strongly heterotrophic system, and resulted in high CO2 efflux to the atmosphere. CH4 concentrations were also higher during the rainy than dry season (93.5 ± 62.5 vs. 61.3 ± 39.5 nmol L −1 ), but unlike p CO2, showed tidal variations similar to TSM and POC, thus alluding to potential CH4 release from sediments during resuspension events at high tidal flow velocities. This explorative survey revealed complex drivers and biogeochemical processes acting upon various spatio-temporal scales which are necessary to consider for a complete understanding of the carbon biogeochemistry in estuarine systems. Similar surveys on estuarine carbon in data scarce regions are encouraged to constrain uncertainties in coastal zone carbon budgets. Highlights: POC, DIC, CO2 and CH4 dynamics were studied in the tropical Guayas river delta. POC likely originated from resuspension of bottom sediments and river basin erosion. DIC did not display conservative mixing with salinity in both dry and rainy seasons. The Guayas delta was oversaturated with CO2, resulting in high water-air efflux. DIC export rate from the Guayas delta to the coastal ocean exceeded that of POC.